MASS RAPID TRANSIT (MRT) DEMAND AND CAPACITY ASSESSMENT FOR RAIL TRANSPORT IN MALAYSIA - Syamsunur, Deprizon; Xiang, Jason Ong Jin; binti Suro, Salihah; Chek, Moon Wei; Retno, Deddy Purnomo; Nelfia, Lisa Oksri; Bt Md Noh, Nur Ilya Farhana; Ng, Jing Lin Ng (Universitas Trisakti, 2024)
Assessing the quality of MRT services unveils a generally satisfactory experience among respondents, with comfort emerging as a particularly noteworthy aspect. Satisfaction levels for MRT service quality range from 3.63 to 4.12, indicating a favorable perception overall. Notably, comfort stands out with the highest satisfaction rating, surpassing the